An exploration of village-level uterotonic practices in Fenerive-Est, Madagascar. Issue 1 (December 2016) - Collins, Lillian; Mmari, Kristin; Mullany, Luke; Gruber, Christian; Favero, Rachel
Abstract Background Pharmaceutical uterotonics are effective for preventing postpartum hemorrhage and complications related to unsafe abortion. In Madagascar, however, traditional birth attendants (Matrones) commonly administer medicinal teas for uterotonic purposes. Little is known about Matrone practices and how they might coincide with efforts to increase uterotonic coverage. The aims of this study were to: 1) identify indications for presumed uterotonic plant use by Matrones, 2) explore uterotonic practices at the village level, and 3) describe the response of health practitioners to village-level uterotonic practices. Methods Twelve in-depth interviews with health practitioners, Matrones and community agents were conducted in local dialect. All interviews were audio-recorded, transcribed, and translated into English for analysis using Atlas.ti. Medicinal plant specimens were also collected and analyzed for the presence of uterotonic peptides. Results While Matrones reported to offer specific teas for uterotonic purposes, health practitioners discussed providing emergency care for women with complications associated with use of specific teas. Complications included retained placenta, hypertonic uterus, hemorrhage and sepsis. Chemical analysis indicated the presence of cysteine-rich peptides in the Dantoroa/Denturus plant used in some Matrones' teas. Conclusions The presence of uterotonic peptides in one plant used by Matrones may indicate that Matrones intend to administer uterotonics for safer childbirth. This finding, combined with practitioner reports of complications related to some medicinal teas, points to a need for availability of an evidence-based uterotonic at the village level, namely, misoprostol pills or oxytocin in the form of uniject.